Mastitis Granulomatosa: Sebuah Tantangan Diagnosis - Dewi, Citra; Amalia, Ella; Kurniawati, Nyiayu Fauziah; Maria Ulfa,, Maria Ulfa,; Pratama, Eka Putra; Murti, Krisna (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2022)
BackgroundGranulomatous mastitis (GM) is often found in reproductive-age women. These patients are treated by the administration ofantituberculosis drugs. It is difficult to determine the exact cause of GM cytologically and histopathologically. Various etiologies i.e.,tuberculosis, sarcoidosis, foreign bodies and immunological diseases may provide granulomatous inflammation features in thetissue. High-sensitivity tests such as PCR can help to detect the presence of Mycobacterium tuberculosis (MT) as one of possibleetiologic agent. Accurate diagnosis will improve the treatment quality thus a better quality of life. The aim of this study was todetermine whether the granulomatous mastitis patients who referred to the Department of Anatomic Pathology Faculty of MedicineUniversitas Sriwijaya/Dr. Moh. Hoesin Palembang Hospital were caused by MT.MethodsA descriptive observational study was performed. Thirty paraffin blocks of GM patients during the period of 1st October 2018 to 29thSeptember 2020 were collected. DNAs were extracted from tissue scrapings of the slides. Then, PCR analysis was conducted usinga specific primer IS6110 with around 200 bp PCR product.ResultsThe mean age of the patients was 40.8 years (range: 23-67 years). There were six samples (20%) of GM produced the expectedamplicon. However, only three of six samples morphologically consistent with tuberculosis.ConclusionGranulomatous inflammatory reactions in the breast are not only caused by tuberculosis. Further study is needed to determine theexact cause of this lesion. Despite high costs, PCR examination may become an alternative approach in determining the etiology ofGM.